2015
DOI: 10.1186/s12885-015-1685-z
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II study of FOLFOX or biweekly XELOX and Erbitux (cetuximab) as first-line therapy in patients with wild-type KRAS/BRAF metastatic colorectal cancer: The FLEET study

Abstract: BackgroundThe clinical benefit of cetuximab combined with oxaliplatin-based chemotherapy remains under debate. The aim of the present multicenter open-label Phase II study was to explore the efficacy and safety of biweekly administration of cetuximab and mFOLFOX-6 or XELOX as first-line chemotherapy in patients with metastatic colorectal cancer.MethodsSixty-two patients with previously untreated KRAS/BRAF wild-type metastatic colorectal cancer were recruited to the study between April 2010 and May 2011. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
4
19
0
1
Order By: Relevance
“…[ 37 ] In fact, some clinical studies demonstrated cetuximab plus XELOX is a effective and tolerable treatment regimen. [ 38 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] In fact, some clinical studies demonstrated cetuximab plus XELOX is a effective and tolerable treatment regimen. [ 38 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only one of the 53 patients was converted from unresectable to resectable. Chemotherapy regimens were chosen according to the IRB‐approved clinical studies, which have been ongoing during the study period . Recently, our first‐line regimens have been oxaliplatin‐based regimens such as mFOLFOX (bolus/infusional fluorouracil and leucovorin with oxaliplatin) or XELOX (capecitabine and oxaliplatin) in combination with anti‐VEGF antibody or anti‐EGFR antibody .…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy regimens were chosen according to the IRB‐approved clinical studies, which have been ongoing during the study period . Recently, our first‐line regimens have been oxaliplatin‐based regimens such as mFOLFOX (bolus/infusional fluorouracil and leucovorin with oxaliplatin) or XELOX (capecitabine and oxaliplatin) in combination with anti‐VEGF antibody or anti‐EGFR antibody . In particular, we selected cetuximab as the anti‐EGFR antibody rather than panitumumab, in combination with standard chemotherapy for KRAS wild‐type metastatic colorectal cancer based on our previous clinical study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paronychia is one of the most common cutaneous adverse event during treatment with cetuximab seen in approximately 10% of the patients. [ 7 8 ]…”
Section: Epidermal Growth Factor-receptor Inhibitorsmentioning
confidence: 99%